Moral Values Internalization to Foster Social Concern Toward Students with Disabilities in Inclusive Schools - Ziyadatul Ilmi; Mohammad Padil; Esa Nur Wahyuni (STAI Syaichona Moh. Cholil Bangkalan, 2025)
The findings in this study describe the process of internalizing moral values in forming social concern of regular students towards students with disabilities in inclusive schools. The approach used is descriptive qualitative, with data collection techniques through observation, supporting documentation, and in-depth interviews with two Islamic Religious Education (PAI) teachers, one Special Assistant Teacher (GPK), and representatives of regular students and students with disabilities. The location of this research was conducted at SMP Bhakti, Malang City, which is an inclusive school with various students, including students with special needs. The findings show that the process of internalizing moral values is carried out through three main stages: value transformation, value transactions, and value transinternalization. The strategies used in this process include teacher role models, positive attitude habits, giving advice, and implementing cooperative learning. The moral values instilled include empathy, tolerance, compassion, and responsibility. Internalization of these values has succeeded in forming a caring attitude of non-disabled students which is reflected in the behavior of respecting, helping, and supporting friends with disabilities in learning and social activities.